Silence and related symptoms in children and adolescents: a network approach to selective mutism - Vogel, Felix; Reichert, Julian; Schwenck, Christina (BMC Psychology, 2022)
Silence in certain situations represents the core symptom of selective mutism (SM). However, it is unclear what additional symptoms are part of this disorder. Although knowledge of symptoms is essential for diagnostics and intervention, to date, only scarce research exists on circumscribed symptoms of SM. Given the large overlap between SM and social anxiety disorder (SAD), it remains also unclear which symptoms can differentiate both disorders.
Gesehen am 21.12.2022